2009
DOI: 10.1099/jmm.0.005587-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of determining β-lactam susceptibility in clinical strains of Pseudomonas aeruginosa

Abstract: One hundred and one randomly selected (2003)(2004)(2005) clinical isolates of Pseudomonas aeruginosa were used to assess the quantitative (MIC) and qualitative (susceptibility category) agreement between the microdilution broth reference method (RM) and disc diffusion (DD), Etest and the VITEK 2 automated susceptibility test system for determination of the susceptibility of P. aeruginosa to piperacillin (PIP), PIP-tazobactam (TZP), ceftazidime (CAZ), aztreonam (ATM) cefepime (FEP) and imipenem (IMP). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Due to this problem, laboratories might consider primary testing of mucoid isolates by disk diffusion. The most notable errors occurred in P. aeruginosa isolates with piperacillin-tazobactam, as has been seen by others (5,7,11,12). Unlike these previous studies that found piperacillin-tazobactam VME rates ranging from 10.2 to 21.7% (5, 7, 10), we found 0 VMEs and only 3 (4.3%) MEs.…”
Section: Discussioncontrasting
confidence: 55%
“…Due to this problem, laboratories might consider primary testing of mucoid isolates by disk diffusion. The most notable errors occurred in P. aeruginosa isolates with piperacillin-tazobactam, as has been seen by others (5,7,11,12). Unlike these previous studies that found piperacillin-tazobactam VME rates ranging from 10.2 to 21.7% (5, 7, 10), we found 0 VMEs and only 3 (4.3%) MEs.…”
Section: Discussioncontrasting
confidence: 55%
“…The Vitek results were confirmed and concordant with disk diffusion testing. Third, a more recent analysis of Vitek 2 performance using the newer (AST-GN69) cards (the same ones our hospital uses) wherein the TZP has been reformulated, were concordant with reference methods [38]. Additionally, an increase in the MICs of cefepime, piperacillin-tazobactam, and ticarcillin-clavulanate was biologically plausible given the antibiotics the patient previously received for the urinary tract infection.…”
Section: Discussionmentioning
confidence: 66%
“…VITEK 2 system showed a high level of minor errors (a tendency toward false sensitivity) particularly to ceftazidime and cefepime. In general, E-test showed a high rate of false-resistant results to all antibiotics among the tested methods, while the disk diffusion method showed a high rate of falsesusceptible results to all antibiotics except ceftazidime (10). broth microdilution method, which showed that only 11 isolates were moderately resistant or resistant to imipenem and meropenem.…”
Section: Resultsmentioning
confidence: 92%